The progress of research on the nexus between food security and biodiversity conservation: a systematic review - Nishigabiraki, Mai; Sekiyama, Takashi (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe current global food system places a high burden on biodiversity, while food production depends on ecosystem services. This study demonstrated the recent progress in research on the link between food security and biodiversity conservation through a systematic review. based on the Web of Science database. A search for the keywords “food security, biodiversity, conservation” yields a mere 1,968 results, accounting for a negligible 0.76% of the results for “biodiversity.” This suggests that academic interest in the relationship between food security and biodiversity conservation remains minimal.MethodsFirst, a literature search was conducted using the keywords “food security, biodiversity, conservation.” The keyword search was performed using the Web of Science database, covering the 10-year period from 2015 to 2024. Next, the 115 papers identified through the review were subjected to cluster analysis using the statistical software R, classifying them according to the themes and methodologies addressed in each paper.ResultsThe first keyword search yields a mere 1,968 results, accounting for a negligible 0.76% of the results for “biodiversity.” This suggests that academic interest in the relationship between food security and biodiversity conservation remains minimal. The results of the cluster analysis classified the 115 papers into five clusters.DiscussionThe findings of this study provide insights into the sustainable transformation of food systems. The recent progress in research on the link between food security and biodiversity conservation demonstrates the advancing integration of biophysical-technical and socio-political approaches. It suggests that we may be getting closer to finding win–win solutions and overcoming the trade-off between biodiversity and food production. On the other hand, despite the growing body of literature directly addressing the nexus between biodiversity and food security, the overall volume of such publications remains limited. Key challenges persist, including the underdevelopment of research on political and economic dimensions, as well as a dearth of studies encompassing the entire food supply chain. The disparities in the number of studies and topics identified in this research serve as indicators of areas where further research is needed. In particular, the promotion of research in the political and economic domains is imperative for the development of a sustainable food system that integrates biodiversity conservation and food security.